Perfecting organization of services on equipment’s repai - S. M. Khairova; A. V. Shimokhin (Вестник СибАДИ)
The article provides relevance of perfecting a system of equipment’s repair, on the basis of specialization of repair services, the author has conducted an analysis of the market of services on repair of metal-cutting equipment in Omsk and other regions which has showed that firms providing these services can't carry out repair in full for the companies therefore it is necessary to keep proper repair service. The authors have considered widespread structure of an organization of repair service of a company, there are identified its disadvantages and there is proposed structure of customer service and possible positive effects from realization of such structure.